Helminths in common eiders (Somateria mollissima): Sex, age, and migration have differential effects on parasite loads. (August 2019) - Vestbo, Stine; Hindberg, Claus; Forbes, Mark R.; Mallory, Mark L.; Merkel, Flemming; Steenweg, Rolanda J.; Funch, Peter; Gilchrist, H. Grant; Robertson, Gregory J.; Provencher, Jennifer F.
Abstract: In birds, parasites cause detrimental effects to the individual host, including reduced survival and reproductive output. The level of parasitic infection can vary with a range of factors, including migratory status, body size, sex, and age of hosts, or season. Understanding this baseline variation is important in order to identify the effects of external changes such as climate change on the parasitic load and potential impacts to individuals and populations. In this study, we compared the infection level (prevalence, intensity, and abundance) of gastrointestinal parasites in a total of 457 common eiders ( Somateria mollissima ) from four different sampling locations (Belcher Islands, Cape Dorset, West Greenland and Newfoundland), and explored the effects of migration, sex and age on levels of parasitism. Across all samples, eiders were infected with one nematode genus, two acanthocephalan genera, three genera of cestodes, and three trematode genera. Migratory phase and status alone did not explain the observed variation in infection levels; the expectation that post-migratory eiders would be more parasitized than pre-migratory eiders, due to the energetic cost of migration, did not fit our results. No effect of age was detected, whereas effects of sex and body size were only detected for certain parasitic taxa and was inconsistent with location. Since gastrointestinal helminths are trophically-transmitted, future studies of the regional and temporal variation in the diet of eiders and the associated variation and infestation level of intermediate hosts might further explain the observed variation of the parasitic load in eiders in different regions. Graphical abstract: Image 1 Highlights: Parasitic infections are understudied for avian populations in the Arctic. The helminth infection level in eiders varied greatly between sites and subspecies. Migratory phase and status alone did not explain observed helminth variation. Inconsistent effects of sex were detected for a few helminth taxa; no effect of age. Future studies investigating associations between diet and parasites are needed.